Prevalence, clinical features and factors associated with psychosis among Idiopathic Parkinson’s disease (IPD) patients in Universiti Kebangsaan Malaysia Medical Centre (UKMMC) - Md Rosli, Najwa Hanim; Abdul Rahman, Abdul Hamid; Mohamed Ibrahim, Norlinah (2016)
Intro: This was a cross sectional study of the prevalence of psychosis and its characteristic in patients with Idiopathic PD (IPD) attending neurology clinic, Pusat Perubatan Universiti Kebangsaan Malaysia (PPUKM).